The Use of Social Networks in Curbing HIV in Higher Education Institutions: A Case Study of the University of Zambia - Daka, Harrison; Jacob, W. James; Kakupa, Paul; Mwelwa, Kapambwe (Scientific Research, 2017)
The AIDS epidemic has affected every aspect of Zambian society and is recognized as the greatest public health challenge of the past 30 years. Nevertheless, education can generate hope in the face of the epidemic using different methods, including social networks. This article investigates the positive and negative impacts of social networks on the spread of HIV at the University of Zambia (UNZA). The research study included survey-based oral interviews with 280 UNZA students. During the course of the study, we realized that efforts have been and are being put in place at UNZA to use online social networks to spread news about HIV and AIDS and how to stop its transmission. Findings showed that most participants felt that social networks hastened the spread of the virus among social media users. Despite social networks having a few positive effects, the results of our study indicate that the negative effects far outweigh the positive effects.
Keywords: Social Networking; Social Media; Facebook; Online Relationships; HIV Education